Prevalence and correlates of antibiotic sharing in the Philippines: antibiotic misconceptions and community‐level access to non‐medical sources of antibiotics. Issue 5 (9th March 2017) - Barber, Daniel A.; Casquejo, Efren; Ybañez, Purita L.; Pinote, Magdaleno T.; Casquejo, Luz; Pinote, Lucia S.; Estorgio, Magdalena; Young, April M.
Abstract: Objective: To identify sociodemographic, knowledge and attitudinal correlates to antibiotic sharing among a community‐based sample of adults (age 18 and older) in a low‐income setting of the Philippines and to explore community‐level data on informal antibiotic distribution in roadside stands (i.e., sari‐sari stands). Methods: Participants ( n = 307) completed self‐administered surveys. Correlates to antibiotic sharing were assessed using logistic regression with Firth's bias‐adjusted estimates. Study staff also visited 106 roadside stands and collected data on availability and characteristics of antibiotics in the stands. Results: 78% had shared antibiotics in their lifetime, most often with family members. In multivariable analysis, agreement with the belief that it is safe to prematurely stop an antibiotic course (OR: 2.8, CI: 1.3–5.8) and concerns about antibiotic side effects (OR: 2.1, CI: 1.1–4.4) were significantly associated with increased odds of reported antibiotic sharing. Antibiotic sharing was not associated with sociodemographic characteristics or antibiotic knowledge. Antibiotics were widely available in 60% of sampled sari‐sari stands, in which 59% of antibiotics were missing expiration dates. Amoxicillin and cephalexin were the most commonly available antibiotics for sale at the stands (60% and 21%, respectively). Conclusions: Antibiotic sharing was common and was associated with misconceptions about proper antibiotic use. Antibiotics were widely available in sari‐sari stands, and usually without expiration information. This study suggests that multipronged and locally tailored approaches to curbing informal antibiotic access are needed in the Philippines and similar Southeast‐Asian countries.